Implementation Of Pre-Marriage Guidance For Prospective Brides In Creating A Sakinah, Mawadah, Warahmah Family At The Karangtengah District, Cianjur - Iwan Gustiawan Fadwi; Iden Nurul Ihsan (Doctoral Program of Social Science Pasundan University, 2026)
This research is motivated by the low level of participation of prospective brides and grooms in participating in pre-marital guidance at the KUA of Karangtengah District. Obstacles that arise include limited time, facilities, and human resources. This study aims to: (1) describe the implementation of pre-marital guidance, (2) identify supporting and inhibiting factors, and (3) determine the perceptions of prospective brides and grooms towards the program. The research method used is qualitative with a descriptive approach. Data were obtained through observation, interviews, and documentation, then analyzed descriptively qualitatively. The results of the study indicate that pre-marital guidance at KUA Karangtengah includes aspects of the mentor, participants, materials, and methods. Supporting factors include infrastructure, facilitator competence, and participant enthusiasm. Inhibiting factors include limited time and busy participants. In general, prospective brides and grooms have a positive perception of pre-marital guidance as an important provision in building a household towards a sakinah, mawaddah, warahmah family.